Heat and mass transfer analysis of nanofluid over linear and non-linear stretching surfaces with thermal radiation and chemical reaction - Sreedevi, P.; Sudarsana Reddy, P.; Chamkha, Ali.J. (Powder technology, 2017)
This article presents MHD heat and mass transfer flow of nanofluid over linear and non-linear stretching sheets embedded in porous media under the influence of Brownian motion, thermophoresis, thermal radiation and chemical reaction. Appropriate transformations reduce the non-linear partial differential systems into ordinary differential equations. Galerkin Finite element method is employed to solve these momentum, temperature and concentration equations numerically subject to the boundary conditions. The influence of various pertinent parameters on velocity, temperature and concentration profiles of the fluid is discussed and the results are plotted through graphs. Furthermore, skin-friction coefficient, Nusselt number and Sherwood number are investigated in detail and results are shown in tabular form. It is concluded that the velocity and temperature profiles escalate, whereas concentration profile depreciates when Brownian motion parameter rises. [Display omitted] •Temperature profiles are elevated, however, velocity profiles decline with (M).•Temperature and concentration profiles heighten when (Nr) rises.•The rates of velocity depress with higher values of (Nb).•As (Nt) rises the temperature, concentration of the fluid rises.